THE EFFECT OF PROCEDURAL JUSTICE, QUALITY OF WORK LIFE, AND INTRINSIC WORK MOTIVATION ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR AND THEIR IMPACT ON HONORER TEACHER PERFORMANCE IN PANGKALPINANG - Afrizal Afrizal; Arjuna Arjuna; Suhardi Suhardi; Ahmad Yani (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
This study aims to examine the effect of procedural justice, quality of work life, and intrinsic work motivation on organizational citizenship behavior and their impact on the performance of honorary teachers in Pangkalpinang. Research respondents are honorary teachers in the city of Pangkalpinang Bangka Belitung as many as 127 people. The sampling technique is stratified random sampling. Model development using structural modeling. Data processing using structural equation model (SEM). The results of the study concluded that there was a relationship between procedural justice, quality of work life and intrinsic work motivation with the performance of honorary teachers; further studies also conclude that there is a relationship between procedural justice and quality of work life, and intrinsic work motivation with organizational citizenship behavior; The study also confirms that there is a relationship between organizational citizenship behavior and teacher performance; Organizational citizenship behavior mediates the relationship between work motivation and teacher performance, the results of the analysis conclude that Organizational citizenship behavior can mediate the relationship between work motivation and teacher performance; Organizational citizenship behavior mediates the relationship between procedural justice and teacher performance, the results of the analysis conclude that Organizational citizenship behavior can mediate the relationship between procedural justice and teacher performance;.